2000
DOI: 10.1034/j.1600-0722.2000.108005359.x
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial morphology, dental occlusion, tooth eruption, and dental maturity in boys of short stature with or without growth hormone deficiency

Abstract: The aim of this project was to study the craniofacial morphology, dental occlusion, dental maturation and tooth eruption in short-statured boys with growth hormone secretion ranging from low to high. The measurements from lateral and posteroanterior cephalograms, orthopantomograms and plaster models were used. Almost all linear measurements of the facial structures were significantly smaller. A disproportionate growth in the cranial base structures as well as in the jaws resulted in facial retrognathia, a prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 18 publications
5
71
0
5
Order By: Relevance
“…The authors explained this fact by a considerable delay in dental age at the beginning of treatment. Kjellberg et al [2], observed in their own studies on a group of short stature boys, that dental age was delayed by about 1 year, which was also confirmed by other authors [3][4][5]. There is also the opinion in the study by Van Erum et al [27] that treatment with GH does not markedly affect the mean value of dental age.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The authors explained this fact by a considerable delay in dental age at the beginning of treatment. Kjellberg et al [2], observed in their own studies on a group of short stature boys, that dental age was delayed by about 1 year, which was also confirmed by other authors [3][4][5]. There is also the opinion in the study by Van Erum et al [27] that treatment with GH does not markedly affect the mean value of dental age.…”
Section: Discussionsupporting
confidence: 71%
“…There is some information in the literature that dental age is delayed in short stature children; the replacement of deciduous teeth by permanent teeth is also delayed, and newly erupted permanent teeth often require orthodontic treatment. Applying hormonal therapy positively affects the process of replacement of dentition [2,3,4,5,6]. Objectives.…”
mentioning
confidence: 99%
“…16,17 In Japan, GH therapy was approved only for managing GHD in specific child chronic diseases in 1975 and for managing Turner syndrome accompanied by GHD in 1990.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is recognized that the mechanisms that regulate craniofacial growth and development include complex interactions between genes, hormones, nutrients, and epigenetic factors that produce the final craniofacial morphology, and any disturbances in this mechanism may result in a deviating growth pattern. 11,12 However, according to the literature, it is unknown whether prematurely born children are at risk of altered craniofa- cial morphology. 8 Therefore, the aim of this study was to evaluate the craniofacial morphology in extremely and very preterm born 8-to 10-year-old children and to compare these findings with those in matched fullterm born controls.…”
Section: Introductionmentioning
confidence: 99%